Bioactivity-maximized herbal tea formulation from banana leaf and other Musa acuminata AAA by-products using D-optimal mixture design - Dung Ha Thi; Hue Cao Thi; Doan Trang Tran Y; The Vinh Mac (Applied Food Research)
Banana leaf, being non-toxic, is often used in traditional cooking and medicine. However, its full potential is still largely unexplored. The current work aimed to screen for biological active compounds in banana leaf, and to establish an optimal formulation of tea using banana leaf and other banana by-products via a mixture design methodology. Obtained results show that banana leaf contains bioactive compounds (polyphenols, flavonoids, tannins, terpenoids), suitable for tea production. Using d-optimal-mixture-design, the optimal formulation (53% banana leaf, 30% peel, 16% corm, 1% sweet grass) was chosen for maximizing achieved total phenolic content, DPPH-inhibition and customers’ acceptance. Predicted and observed values were found to be in good agreement, pointing to the good-quality of the model. Additionally, the product met WHO-recommended limits for heavy metals and microbial contamination, assuring product safety. These findings indicate that Musa acuminata AAA by-products possess great potential as alternative sources of antioxidants for tea production.